Permeate fluxes from desalination of brines and produced waters: A reactive transport modeling study - Sergi Molins; Nicolas Spycher; Sarah M. Dischinger; Mostafa Nassr; Ji Yeon Lee; Jacob Johnston; Nils Tilton; Kristofer L. Gleason; Benny D. Freeman; William T. Stringfellow; Daniel J. Miller (Applied Geochemistry, 2025)

Domestication and evolutionary histories of specialized gut symbionts across cephalotine ants - Christian Cabuslay; John T. Wertz; Benoît Béchade; Yi Hu; Sonali Braganza; Daniel Freeman; Shreyansh Pradhan; Maria Mukhanova; Scott Powell; Corrie Moreau; Jacob A. Russell (Molecular Ecology, 2024)
The evolution of animals and their gut symbionts is a complex phenomenon, obscured by lability and diversity. In social organisms, transmission of symbionts among relatives may yield systems with more stable associations. Here, we study the history of a social insect symbiosis involving cephalotine ants and their extracellular gut bacteria, which come predominantly from host‐specialized lineages. We perform multi‐locus phylogenetics for symbionts from nine bacterial orders, and map prior amplicon sequence data to lineage‐assigned symbiont genomes, studying distributions of rigorously defined symbionts across 20 host species. Based on monophyly and additional hypothesis testing, we estimate that these specialized gut bacteria belong to 18 distinct lineages, of which 15 have been successfully isolated and cultured. Several symbiont lineages showed evidence for domestication events that occurred later in cephalotine evolutionary history, and only one lineage was ubiquitously detected in all 20 host species and 48 colonies sampled with amplicon 16S rRNA sequencing. We found evidence for phylogenetically constrained distributions in four symbionts, suggesting historical or genetic impacts on community composition. Two lineages showed evidence for frequent intra‐lineage co‐infections, highlighting the potential for niche divergence after initial domestication. Nearly all symbionts showed evidence for occasional host switching, but four may, more often, co‐diversify with their hosts. Through our further assessment of symbiont localization and genomic functional profiles, we demonstrate distinct niches for symbionts with shared evolutionary histories, prompting further questions on the forces underlying the evolution of hosts and their gut microbiomes.

Population expansion and intensification from a Malthus-Boserup perspective: A multiproxy approach in Central Western Argentina - Eva A. Peralta; Jacob Freeman; Adolfo F. Gil (Quaternary International, 2024)

A streamlined approach to characterize microalgae strains for biomass productivity under dynamic climate simulation conditions - Nathan Beirne; Scott Edmundson; Song Gao; Jacob Freeman; Michael Huesemann (Algal Research, 2023)

DISCOVR strain pipeline screening – Part I: Maximum specific growth rate as a function of temperature and salinity for 38 candidate microalgae for biofuels production - Michael Huesemann; Scott Edmundson; Song Gao; Sangeeta Negi; Taraka Dale; Andrew Gutknecht; Hajnalka E. Daligault; Carol K. Carr; Jacob Freeman; Theresa Kern; Shawn R. Starkenburg; Cheryl D. Gleasner; et al. (Algal Research, 2023)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Modelling potential Pleistocene habitat corridors between Afromontane forest regions - Kaitlin E. Allen; Walter P. Tapondjou; Benedictus Freeman; Jacob C. Cooper; Rafe M. Brown; A. Townsend Peterson (Biodiversity and Conservation, 2021)

Mutualism Wildlife Value Orientations Predict Support for Messages About Distance-Related Wildlife Conflict - Stephanie Freeman; B. Derrick Taff; Zachary D. Miller; Jacob A. Benfield; Peter Newman (Environmental Management, 2021)

Molecular changes in transcription and metabolic pathways underlying muscle atrophy in the CuZnSOD null mouse model of sarcopenia - Kavithalakshmi Sataranatarajan; Gavin Pharaoh; Jacob L. Brown; Rojina Ranjit; Katarzyna M. Piekarz; Kaitlyn Street; Jonathan D. Wren; Constantin Georgescu; Caroline Kinter; Michael Kinter; Willard M. Freeman; Arlan Richardson; et al. (GeroScience, 2020)

Neuroglial Expression of the MHCI Pathway and PirB Receptor Is Upregulated in the Hippocampus with Advanced Aging - Heather D. VanGuilder Starkey; Colleen A. Van Kirk; Georgina V. Bixler; Caesar G. Imperio; Vijay P. Kale; Jacob M. Serfass; Julie A. Farley; Han Yan; Junie P. Warrington; Song Han; Matthew Mitschelen; William E. Sonntag; et al. (Journal of Molecular Neuroscience, 2012)

Y chromosome haplogroups and prostate cancer in populations of European and Ashkenazi Jewish ancestry - Zhaoming Wang; Hemang Parikh; Jinping Jia; Timothy Myers; Meredith Yeager; Kevin B. Jacobs; Amy Hutchinson; Laurie Burdett; Arpita Ghosh; Michael J. Thun; Susan M. Gapstur; W. Ryan Diver; et al. (Human Genetics, 2012)

Domesticated crop richness in human subsistence cultivation systems: a test of macroecological and economic determinants - Jacob Freeman (Global Ecology and Biogeography, 2012)
Aim To describe patterns of crop richness at a global scale and investigate the potential influence of energy, water, habitat heterogeneity, area and economic commitment to agricultural practices on patterns of crop species richness. Location World‐wide. Methods Ethnographic literature for 86 subsistence‐oriented societies was surveyed; 55 of these societies grow crops and 31 do not. These 86 societies occupy the range of latitudes at which subsistence‐oriented groups manage domesticated plant species. The number of domesticated plants that each society cultivates is reported. Regression analyses were conducted to evaluate predictions for relationships between crop richness, energy, area, habitat heterogeneity, commitment to cultivation and species taxonomic descriptions. Results Crop richness is positively and significantly related to energy availability and commitment to cultivation. The warmer the environment in which cultivators live, the more crop species cultivators grow. The more subsistence farmers commit to cultivation, the more crop species subsistence farmers grow. Above a threshold of 500 m in elevation range, crop richness is positively related to topographic heterogeneity. Mean annual rainfall, elevation, area, commitment to domesticated animals and exchange are not significantly related to crop richness. Main conclusions Crop richness in subsistence‐oriented farming systems is conditioned by energy availability via the physiological tolerances of crop species. Crop richness is secondarily conditioned by topographic heterogeneity, which may serve as an estimate of spatial climatic heterogeneity. Where energy availability is a relatively weak constraint on crop production, commitment to cultivation for subsistence strongly conditions how much effort producers invest in diversifying their crop base. It is postulated that tolerance to freezing temperatures limits the ranges of domesticated plant species. This range limitation might be the result of niche conservation among domesticated crop species and a legacy of greater rates of speciation and lower rates of extinction among ‘free living’ species in tropical settings.